Developing seismic risk assessment and prediction of building's vulnerability : case study of residential area of yogyakarta, indonesia - Adi Setiabudi, Bawono (2024)
Indonesia is located in an earthquake-risk-prone area. One opportunity to mitigate and minimize the earthquake impact is understanding the phenomena. Conducting seismic risk assessment can insist on mitigating the potential risk. Recently in Indonesia, the Hazard United States (HAZUS) method was frequently used in conducting the Seismic Risk Assessment (SRA). From the literature review, HAZUS needs to be adapted according to the regional conditions, building materials and local earthquake records. The localized input may influence the outcome of the assessment. Furthermore, numerous agencies have proposed a guideline process for conducting a seismic risk assessment in Indonesia. In addition, the complexity of the assessment also involves the local parameter, especially the building types. Therefore, in managing the situation, this study looked at possibilities, Damage Probability Matrix (DPM) for Indonesia typical building based on mapping damage state estimate to vulnerable function compatible building type from HAZUS, to succeed the DPM derived traditionally harmonised damage states threshold to HAZUS. In addition, the main objective of this study is also to improve the criteria assessment base on local parameters. In consequence, the first step is to identify and harmonise the damaged state criteria from six (6) different agencies in Indonesia. Further, DPM was developed based on expert judgement by using Fuzzy Analytic Hierarchy Process (FAHP). In advance, the developed cumulative probabilistic and DPM from the HAZUS were compared to assess the proposed DPM. From the results, new damage state criteria were proposed, ranked, and a few criteria were eliminated based on expert judgement. The new DPM based on the previous result was developed with the updated criteria. DPM from HAZUS was developed and compared. DPM proposed was identical, following the trend of DPM in HAZUS for Reinforced Concrete Moment Resisting Frames-Low Rise (C1L). Based on the observation, this result can be accepted to be used. However, the percentage difference range is between -35.52 per cent to 68.39 per cent. Therefore, the findings indicate that while HAZUS is reliable as a standard of evaluation, adjustments are needed to align buildings evaluated using expert judgement with the FAHP to the HAZUS C1L model. Additionally, adapting the HAZUS model for other countries requires careful consideration of differences in hazards, risks, construction practices, building laws, materials, data availability, and damage thresholds. Thus, significant modifications may be necessary to ensure accuracy and effectiveness. It can be concluded the usage of HAZUS needs to be adaptable to the scenario cases at a specific location. Further study is encouraged to improve the damage state criteria, especially in Indonesia. Overall, this is a novel study because it is possible to harmonize the categories and criteria for damage in Indonesia from various agencies, which has never been done before, using the expert judgment method with FAHP as the model. Furthermore, this study examines how substantial the difference is between the expert judgment method and FAHP in searching for the Damage Probability Matrix based on the most recent seismic zones and regulations as assessed by assessor with experience.